Do velho ao novo: política e educação no Maranhão - Pinto, Maria Núbia Bonfim (1982)
This dissertation aims analysing the educationa1 policy of the Sarney administration in the State of Maranhão for 1966 to 1970. When Sarney begins his governement he conditions his program to be development lines already adopted in the Southern part of Brazil. He proposes a 'new Maranhão', ba sed on industrial and on agriculture and cattle - raising projects which were to be supported by an infrastructure in troduced and/or maintained by means of governamental incentives. In such a context, the educational sector is called in to perform an important series of functions, from the ideological inculcation of the 'new' idea action the developmental plans for the State. This study identifies education as a politica1 element by excellence, to be employed in a situation like that. In this period most of the educational projects are characterized by a certain immediacy as well an by bold proproposals, and are consistent with other similar governamental projects, guarding no relationship with the multiple and diversified reality of Maranhão.